That half of the room is yours: conflict behavior systems in a university residence hall - Mueller, Christopher (Kansas State University, 2014)
College residence halls house thousands of students every year. This provides students an opportunity to live closely with new people and develop social skills sought by employers (Myers & Larson, 2005). Living with new people also provides the opportunity for anxiety and conflict (Ingalls, 2000). Many residents reject the idea of initiating or processing their own conflicts, often turning to destructive conflict management behaviors such as avoidance (De Cecco & Richards, 1974; Sillars, 1980). A clearer understanding of influences on student conflict behaviors will help colleges and universities assist students in having positive experiences living on campus. While attempts to understand student conflict management are varied, few consider behavior patterns as systems (Duran & Zakahi, 1988, Kiernan & Gray, 2013, Martin & Anderson, 1995). This qualitative study applies an organizational communication framework and structuration theory (Giddens, 1984; Poole & McPhee, 2005; Sewell, 1992) as a lens to address conflict behavior systems and structures within post-secondary residence halls. Theoretically, this research adds to existing scholarship by applying structuration theory to a non-business context, extending the theory beyond the employer/employee dynamic it is often constrained to. Additionally this study uses structuration theory in a practical manner (Sewell, 1992) in the hopes of informing and improving roommate pairing and conflict approaches. Twenty-three student residents participated in in-depth interviews to answer research questions designed to address communication practices that relate to rules and resources of conflict structures as well as how the dimensions of structuration, power, meaning, and norms, influence the use of rules and resources (Poole & McPhee, 2005). The study identifies resources of authority, space, favor reciprocity, mutual respect, routines, external others, and time and discusses the associated rules within college residence hall rooms. These rules and resources are informed by systems of “coexistent” and “engaged” harmony. Additionally the study identifies how the dimensions of structuration shape systems within the residence hall room and between the roommates by influencing the way rules and resources are used. Largely, this study contributes to the field of structuration research while attempting to incorporate pieces of Sewell’s (1992) critique in the form of practical implications.
Keywords: Structuration; Conflict; Roommates; Residence Hall; Communication; Systems; Communication (0459); Higher Education (0745)